Literacy mediation as a form of powerful literacies in community-based organisations working with young people in a situation of precarity. Issue 2 (3rd May 2016) - Thériault, Virginie
Abstract : This paper aims at understanding the complex relations between bureaucratic literacies, the lives of young people in a situation of precarity and the work of employees of two community-based organisations in Québec (Canada). Drawing on the perspective of the New Literacy Studies, the focus of this article is around the role of literacy mediators that can play youth workers. It also endeavours to clarify the meaning of the term precarity ( précarité ) by suggesting a multidimensional perspective on it. This paper reveals that literacy mediation can be a form of powerful literacies that offer opportunities to counteract dominant literacies and support new ways of learning. Finally, it suggests a reflection on the importance of the work of community-based organisations in countering the situation of precarity experienced by some young people. It underlines the fact that these organisations are also experiencing financial uncertainty and insecurity that affect their services.